The Relationship between Personal Traits and Accounting Students Perception on Ethics and Love of Money: Case of Malaysian Government-Linked University - Esa, Elinda; Zahari, Abdul Rahman (Journal of Asian Business Strategy, 2015)
Ethical crises occur in all professions, affecting not only those already in the profession, but also those preparing to enter it. The accounting profession experienced controversial the deepest crisis in its history with the discovery that accountants had acceded in historic fictitious financial reporting by corporate giants such as Enron, WorldCom, Tyco, Parmalat and others. The long term destruction inflicted on these professions is still being felt. However the view among those preparing to enter their particular profession, e.g. they are enrolled in a police academy, seminary, college or higher learning institution, is a crucial significance. Since the accounting students will be the future members of the accounting profession and are prone to be involved literally in the corporate scandals, their ethical behavior can be used to measure ethical conduct. Thus, using primary data collection through questionnaire survey on accounting students in one of the Malaysian government-linked university and partial least square (PLS) tool, the aims of the study is to investigate the influence of personality traits towards love of money (perception to money) and ethics.